The clinical applications of drugs and their metabolites analysis in biological fluids and commonly used analytical techniques for bioanalysis: review - Mekonnen, Biset Asrade; Yizengaw, Muluabay Getie; Adugna, Kebede Feyisa (Frontiers in Analytical Science, 2024)
This study provides an overview of the clinical applications of drugs and their metabolites analysis in biological fluids and identifies commonly used analytical techniques for bioanalysis.Original open-access articles published between October 31, 2005, and October 31, 2020, in Google Scholar, MEDLINE, PubMed, and Embase were reviewed, and pertinent findings of the individual studies were pooled and presented using tables. This review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Results: Fifteen studies met the eligibility criteria and were included in the review. These studies show that qualitative identification and quantitative determination of drugs and their metabolites in biological fluids are important for therapeutic drug monitoring (TDM), pharmacokinetic and pharmacodynamic studies, drug abuse control, and forensic and toxicological analyses. Spectroscopic, electrochemical, and hyphenated and nonhyphenated chromatographic techniques are used to analyse drugs and their metabolites in biological fluids. However, hyphenated techniques are the preferred analytical methods because of their sensitivity, selectivity, accuracy, reproducibility, efficiency, and rapid analysis.Bioanalysis is important for pharmacokinetic and pharmacodynamic studies, therapeutic drug monitoring, forensic and toxicological analyses, and drug abuse control using different bioanalytical techniques. However, hyphenated techniques are the most commonly used bioanalytical techniques. Bioanalysis of drugs and their metabolites needs to be improved to provide good medical and pharmaceutical care to patients, to confirm forensic and toxicological cases, and to control drug abuse.